Management of Lecturers Performance Assessment Improving The Quality of Higher Education Academic at Syekh Yusuf Islamic University Tangerang - Sukanti, Lina (The International Journal of Education Management and Sociology, 2023)
This Research aims to determine the management of lecturer performance appraisal and the steps of lecturer performance in quality improvement. The research method uses a qualitative approach to describe lecturer performance. Data collection techniques through (1). in-depth interviews with the quality assurance unit as the main informant, senior lecturers, and the dean, (2). Observation observing the events at the research location. (3). Documentation studies include meeting notes, photos of activities, lecturers' scientific work, and those related to the research focus. The conclusion is that management of lecturer performance evaluation, including lecturer performance assessment in Teaching, Research, and community service, has been carried out through the stages of planning, organizing, implementing, and supervising. Lecturer performance can improve the quality of Higher Education. Systematic lecturer performance can enhance academic quality. Based on an integrated value data system in the educational section in each semester, with very good accreditation, a cumulative grade point index of 3.5 with lecturer performance fulfilling lecturer certification and available positions. Based on LAM-PT accreditation. That the Faculty of Teacher Training and Education in the English Language Study Program and Economics Education is Very Good, fulfilling the indicators of human resources, education, Research, and community service